Evaluasi Kinerja Keuangan PT Indofood CBP Sukses Makmur Tbk Berdasarkan Laporan Keuangan - Ashar basyir; Dini Andriyani; Aldila Kurnia Dian Permata Sari; Noor Muhammad Adipati (Jurnal Aplikasi Perpajakan, 2025)
This study aims to examine the financial performance of PT Indofood CBP Sukses Makmur, Tbk based on financial statement analysis for the 2022–2024 period. The study employs a descriptive quantitative method using secondary data in the form of the company’s financial statements for the 2022–2024 period obtained from the Indonesia Stock Exchange and the company’s official website. Data were collected through literature review and documentation, and subsequently analyzed using the Cash Coverage Ratio to Interest (CKB), Cash Coverage Ratio to Current Liabilities (CKHL), and Capital Expenditure Ratio (PM) to assess the company’s financial performance. The results indicate that the financial performance of PT Indofood CBP Sukses Makmur, Tbk during the 2022–2024 period, based on the analysis of the Cash Coverage Ratio to Interest (CKB), Cash Coverage Ratio to Current Liabilities (CKHL), and Capital Expenditure Ratio (PM), experienced fluctuations but generally remained in a safe condition. This indicates that the company is able to meet its short-term obligations, cover interest expenses, and maintain cash flow stability to support capital expenditures and business sustainability.